Biocultural Diversity of the Endemic Wild Jack Tree on the Malabar Coast of South India - Sam P. Mathew, A. Mohandas, S. M. Shareef and G. M. Nair
Artocarpus hirsutus Lam. is an endemic tree species of the southern Western Ghats of Peninsular India. It is popularly known as the `wild jack tree". Several attributes inart, culture and socio-economic civilization among the folk communities in Kerala state (Malabar coast) distinguish the tree in the history of Indian civilization. Most of the traditional uses and indigenous know-how earlier referred to this species are vanishing. This article discusses various aspects of the popular wild jack tree of the Malabar coastand its vanishing indigenous biocultural diversity among the folk communities of the region.